Synthesis and boron interaction of new amino acid containing phthalocyanines and the precursor - Baseren, Sukran Cenikli; Erdogmus, Ali; Gul, Ahmet (ELSEVIER SCIENCE SA, 2018)
A new phthalonitrile precursor with tyrosine substituent and the zinc phthalocyanine derived from it were synthesized and their interaction with diphenylborinic acid was studied. The new compounds were characterized by using elemental analysis, IR, H-1 and B-11-NMR and UV-VIS spectral data. B-11-NMR data demonstrated that boron atom attached to the phthalonitrile precursor is in a bulky tetra-coordinated state with the formation of a coordinative N-B bond while completely planar phthalocyanine moieties with high aggregation tendencies at the concentrations used in NMR measurements lead the borinic ester side of the molecule into a planar tri-coordinated form. Moreover, the consequences of the presence of diphenylborinic ester groups on the spectral, photophysical and photochemical properties of the new zinc phthalocyanine are investigated in detail. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Phthalocyanine; Diphenylborinic acid; Borinate complex; Photochemistry; Fluorescence; ZINC PHTHALOCYANINE; PHOTOCHEMICAL PROPERTIES; COMPLEXES; ESTER; Chemistry